Current complications and treatment of aspirin-exacerbated respiratory disease. (1st December 2016) - Cook, Kevin A.; Stevenson, Donald D.
ABSTRACT: Introduction : Aspirin-exacerbated respiratory disease is defined by the clinical tetrad of aspirin sensitivity, nasal polyps, asthma, and chronic rhinosinusitis. Patients experience acute upper and lower airway reactions with exposure to aspirin and other cyclooxygenase-1 inhibiting medications. However, airway inflammation and disease progression occur even in the absence of exposure to these medications, often leading to aggressive polyp formation and need for systemic corticosteroids to treat exacerbations in asthma and rhinosinusitis. Areas c overed : This review focuses on the direct and indirect complications of aspirin-exacerbated respiratory disease. Current and potential management strategies are discussed with emphasis on aspirin desensitization. Expert c ommentary : Aspirin desensitization remains the gold standard of treatment. Demonstrated benefits of desensitization include improved symptom scores, reduction in use of systemic corticosteroids, slowing of polyp regrowth, and tolerance of aspirin and other NSAIDs for various therapeutic purposes. Continued investigation into the pathogenic mechanisms of AERD is likely to yield new diagnostic and therapeutic approaches.